Dampak Lapisan Konstruksi Atap terhadap Suhu Ruang - Nurul Fitria Marina (Universitas Muhammadiyah Surabaya, 2020)
AbstractThe roof is a cover on a building that protects inside of the building from various situations and weather. The roof layer affects its ability to protect the space underneath. The use of roof insulation can reduce the heat coming from the roof. This is because the roof is in direct contact with the hot sun. Not only hot, but roof insulation is also able to reduce sounds such as the sound of raindrops on the roof. There are various materials that function as roof insulation, one of which is styrofoam. Styrofoam is indeed prohibited as a container for food, but the structure contained in Styrofoam is able to reduce heat with hollow grains so that it can withstand the heat. Styrofoam is now starting to become a favorite for the public in reducing heat due to its affordable price and easy access. However, the use of Styrofoam as an insulator on the roof should be supported by other construction layers both on the walls and floors so that room temperature cooling can be optimal. Keywords: construction, roof, thermal, environment, building. AbstrakAtap merupakan penutup atas suatu bangunan yang melindungi bagian dalam bangunan dari berbagai situasi dan cuaca. Lapisan atap mempengaruhi kemampuannya dalam melindungi ruang di bawahnya. Penggunaan insulasi atap mampu meredam suhu panas yang berasal dari atap. Hal ini dikarenakan atap bersinggungan langsung dengan panas matahari. Tidak hanya panas, namun insulasi atap juga mampu meredam suara seperti suara rintik hujan pada atap. Terdapat berbagai bahan yang berfungsi sebagai insulasi atap, salah satunya styrofoam. Styrofoam memang dilarang sebagai wadah pada makanan, anmun struktur yang terdapat pada Styrofoam mampu meredam panas dengan butiran berongga sehingga mampu menahan panas. Styrofoam saat ini mulai menjadi favorit bagi khalayak dalam meredam panas dikarenakan harganya yang terjangkau dan mudah mendapatkannya. Namun, penggunaan Styrofoam sebagai insulator pada atap sebaiknya didukung oleh lapisan konstruksi lainnya baik pada dinding maupun lantai agar pendinginan suhu ruang dapat optimal. Kata Kunci: konstruksi, atap, termal, lingkungan, bangunan